EFEKTIFITAS REBUSAN DAUN SALAM TERHADAP PENURUNAN KADAR ASAM URAT PADA PENDERITA GOUT PUSKESMAS REJOSARI PEKANBARU - Yesi Septina Wati; Komaria Susanti; Ika Permana Sari (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
ABSTRACT High uric acid, known as Gout, is a disease caused by purine metabolism disorders (hyperuricemia) which will cause crystal buildup in joints and blood vessels. The buildup of crystals will cause pain, swelling, inflammation and stiffness in the joint area.One of the non-pharmacological therapies that can be done is consuming bay leaf decoction. The purpose of this study was to investigate the effect of giving bay leaves stew water to reduce uric acid levels in Gout sufferers in the Rejosari Public Health Center Working Area, Pekanbaru City. This wasquasy experiment reasearch with pre and post test with control group design. The sampling method was purposive sampling. The number of obtained participants were 24 respondents. Independent T Test was performed to analyse reasearch data. The result after seven days intervention showed that the difference of uric acid levels in contol and intervention groups was 2.43 gr/dl with p value is 0.000. It can be concluded that there is an effect of giving decoction water of bay leaves on reducing uric acid levels among Gout patients in Rejosari Public Health Center Working Area, Tenayan Raya Sub-District, Pekanbaru City. It is expected that gout patients can consume decoction water bay leaves as alternative treatment for gout.